The Role of Artificial Intelligence in Building a Culture of Knowledge Sharing among Students and University Students - Suarni Norawati; Akmal Andri Yantama; M. Zacky (Jurnal Sistem Cerdas, 2025)
This study examines the role of Artificial Intelligence (AI) in fostering a culture of knowledge sharing and enhancing knowledge management among students and university learners in the digital learning environment. Using a quantitative explanatory approach, data were collected from 100 respondents who actively used AI-based applications such as ChatGPT, Grammarly, and Copilot in their academic activities. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results reveal that AI has a significant direct effect on knowledge management (β = 0.316, p = 0.000) and a strong positive influence on knowledge sharing behavior (β = 0.851, p = 0.000). Furthermore, knowledge sharing significantly mediates the relationship between AI and knowledge management (β = 0.611, p = 0.000), indicating that AI’s greatest impact occurs through the enhancement of collaborative knowledge exchange among learners. The model explains 80.3% of the variance in knowledge management and 72.3% in knowledge sharing, demonstrating strong predictive power. These findings highlight AI’s potential as a collaborative catalyst that strengthens human-centered learning ecosystems. The study contributes both theoretically by extending the understanding of AI-mediated knowledge processes—and practically by providing insights for educators to integrate AI ethically and effectively into knowledge-based learning systems